2018
DOI: 10.1126/science.aar3593
|View full text |Cite|
|
Sign up to set email alerts
|

Pan-tumor genomic biomarkers for PD-1 checkpoint blockade–based immunotherapy

Abstract: INTRODUCTION: Immunotherapy targeting the programmed cell death protein–1 (PD-1) axis elicits durable antitumor responses in multiple cancer types. However, clinical responses vary, and biomarkers predictive of response may help to identify patients who will derive the greatest therapeutic benefit. Clinically validated biomarkers predictive of response to the anti–PD-1 monoclonal antibody pembrolizumab include PD-1 ligand 1 (PD-L1) expression in specific cancers and high microsatellite instability (MSI-H) rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,488
5
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,790 publications
(1,657 citation statements)
references
References 61 publications
61
1,488
5
8
Order By: Relevance
“…This suggests that the higher degree of T‐cell activation associated with 4‐1BB expression may reflect a robust antitumor response that leads to improved survival outcomes in HCC patients. Furthermore, HCCs with higher 4‐1BB signature expression showed enrichment of the T‐cell–inflamed gene signature, suggesting that 4‐1BB–related T‐cell activation directs active IFN‐γ and cytotoxic antitumor T‐cell responses, which are also associated with anti–PD‐1 response . This gene set will be an important resource for mining additional key genes and pathways involved in T‐cell activation against HCC.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that the higher degree of T‐cell activation associated with 4‐1BB expression may reflect a robust antitumor response that leads to improved survival outcomes in HCC patients. Furthermore, HCCs with higher 4‐1BB signature expression showed enrichment of the T‐cell–inflamed gene signature, suggesting that 4‐1BB–related T‐cell activation directs active IFN‐γ and cytotoxic antitumor T‐cell responses, which are also associated with anti–PD‐1 response . This gene set will be an important resource for mining additional key genes and pathways involved in T‐cell activation against HCC.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, multiomic analyses may provide a more complete patient biomarker profile for guiding treatment decisions. Indeed, other biomarkers commonly investigated alongside TMB include PD‐L1, microsatellite instability (MSI) or deficient mismatch repair, and immune signatures …”
Section: The Future Clinical Landscape Of Tmbmentioning
confidence: 99%
“…18 In a subsequent estimation presented by the authors in the same article, it was shown that serous ovarian cancers were composed mainly of tumors that had low TMB and low GEP (70%-75%) or low TMB and high GEP (20%-25%), and <5% were found to have high TMB.…”
Section: Role Of Tumor-infiltrating Lymphocytesmentioning
confidence: 96%